Impact of diabetes and periodontal status on life quality - Radhika Desai; Bhushan Khobaragade; Giles McCracken; Rebecca Wassall; John J. Taylor; Susan M. Bissett; Andrew S. Pumerantz; Philip M. Preshaw (Nature Publishing Group, 2021)
Abstract Objectives To investigate impact of periodontal status on quality of life (QoL) in type-1 (T1D) and type-2 (T2D) diabetes patients pre- and post-periodontal treatment using the Well-being Questionnaire 12 (W-BQ12) and Audit of Diabetes-Dependent Quality of Life-19 (ADDQoL-19). Methods W-BQ12 and ADDQoL-19 were self-completed by 56 T1D and 77 T2D patients at baseline and by those with periodontitis 3 and 6-months after therapy. Results At baseline, T1D patients had significantly higher general W-BQ12 [Median (IQR); 24.00 (20.25-27.75)] and positive well-being scores [8.00 (6.00-9.00)] (indicating better QoL) compared to T2D patients [22.00 (15.50-26.00) and 6.00 (3.50-9.00)], respectively (p < 0.05). Within both groups, general W-BQ12 scores did not differ significantly between patients with periodontal health, gingivitis, or periodontitis (p > 0.05). Significantly higher general W-BQ12 scores were observed in T1D patients at month 3 [28.00 (22.00-29.50)] compared to baseline [22.00 (17.00-24.50)] (p < 0.01), suggesting an initial improvement in QoL post-treatment. ADDQoL-19 identified that diabetes had greatest impact on the domain 'freedom to eat', with participants placing most importance on 'family life'. No significant changes in ADDQoL-19 scores were seen post-treatment (p > 0.05). Conclusions Diabetes had impacts upon aspects of life quality in both T1D and T2D patients, though any additional impact based on periodontal status was not observed when using W-BQ12 and ADDQoL-19.